EFEKTIVITAS PENGUNAAN MEDIA ANIMASI MOTION DENGAN MODEL PBLTERHADAP KEMAMPUAN BERBICARA SISWA KELAS V - Dewi Koeswanti, Henny; Anggraeni, Cynthia; Emiliana Koehtae, Serli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low speaking ability of students is caused by a lack of self-confidence in students and teachers tend to use inappropriate learning media to help students in the learning process. The aim of this research is to compare the application of the Problem Based Learning learning model based on motion animation media with the Problem Based Learning learning model without motion animation media on the speaking abilities of fifth grade elementary school students. The type of research used is experimental research in the form of Quasy Experimental Design (quasi-experiment). The data collection technique is through tests using instruments to measure speaking ability. The population in this study used the Joko Tingkir Cluster which consisted of 5 schools. The sample in this study was class V students of SDN Tingkir Tengah 01 and SDN Tingkir Lor 01 Salatiga. Based on the results of research data analysis, it was found that the average value of learning outcomes increased, namely from the initial test to 54.80, then in the final test it became 89.20. Through the t-test, a value of 0.000 is obtained, which means 0.05. So it can be said that H0 or the null hypothesis is rejected. So, it can be concluded that motion animation media has proven to be effective on the speaking abilities of V grade elementary school students.